2017
DOI: 10.1002/hup.2620
|View full text |Cite
|
Sign up to set email alerts
|

Utility ofWeb search query data in testing theoretical assumptions about mephedrone

Abstract: The results might provide support for the hypothesis that mephedrone's popularity was highly correlated with its legal status as well as it functioned as a potential substitute for MDMA. Google Trends was found to be a useful tool for testing theoretical assumptions about NPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A study by Kapitány-Fövény and Demetrovics [33] assessed the utility of Google Trends in providing relevant information about the web-interest toward mephedrone. This study confirmed the fact that mephedrone reached its popularity when it was still legal.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Kapitány-Fövény and Demetrovics [33] assessed the utility of Google Trends in providing relevant information about the web-interest toward mephedrone. This study confirmed the fact that mephedrone reached its popularity when it was still legal.…”
Section: Resultsmentioning
confidence: 99%
“…Not only was search query data found to be a valuable proxy measure of the production and use of krokodil, but the volume of search queries related to krokodil were found to substantially increase in immediately following the amplification of media reports and government demonstrations framing krokodil as a significant social problem, while significantly decreasing immediately following the implementation of governmental restrictions on the drug. Similarly, a recent study by Kapitany-Foveny and Demetrovics (2017) indicated that the volume of Internet entries—including search queries, articles published online, and online advertisements—related to the NPD mephedrone is inversely related to its legal status. That is, in the period of time after mephedrone was banned, Internet activity related to the drug increased.…”
Section: Internet Search Queries As Datamentioning
confidence: 95%
“…That is, in the period of time after mephedrone was banned, Internet activity related to the drug increased. The authors note the increased Internet activity surrounding mephedrone was significant, while measures of activity related to drugs such as cocaine, heroin, and ecstasy remained consistent during the same period (Kapitany-Foveny & Demetrovics, 2017). Taken together, these findings highlight both the utility of search query analysis in the study of drug use patterns and the influence of governmental regulations on these same patterns.…”
Section: Internet Search Queries As Datamentioning
confidence: 99%